Effect of Dual External Exhaust System with Activated Charcoal and Reheater on Diesel Engine Exhaust Emissions - muhammad riyadi, muhammad riyadi; Septiyanto, Angga; Wijaya, Burhan Rubai; Roziqin, Ahmad (Universitas Negeri Semarang, 2024)
The increase in the mass and widespread use of diesel engines can lead to an increase in exhaust emissions, which can have a negative impact on the environment and human health with an increase in the number of vehicles and activities in workshops and test sites, there is a need to minimize the emission of exhaust gases during the process, The need for additional alternative methods that can help reduce emissions in places where there are potentially many vehicles in vehicle repair shops vehicle repair shops, at vehicle test sites and light vehicle practice places of automotive vocational high schools,, the development of additional equipment that is attached or added to an object without changing from that object or after treatment tools It is still rarely found, especially in ordinary workshops, even official workshops are still uneven and not optimal, reducing exhaust gas levels when the vehicle stops or is static. This study uses an experimental method by making after treatment tools in the form of dual external exhaust systems that are attached to vehicles during emission testing and testing that emit smoke or vehicle exhaust emissions as an alternative effort in handling vehicle emissions, especially diesel engines. The tool in the form of a dual external exhaust system with activated charcoal and a reheater with temperature variations from the reheater at temperatures of 100 °C, 150 °C, and 250 °C is used in conventional diesel vehicles and common rail diesel vehicles. Tests are taken 3 times on each specimen/variation. The results of this study show that first, there is an effect of dual external exhaust systems with activated charcoal and reheater on the exhaust gas emissions of conventional diesel engines, the effect obtained is a decrease in CO emission results from 0.47 to 0.10 with a percentage decrease of 78% and Opacity from 82 to 46 with a percentage of 44%. Then the second is the influence of dual external exhaust systems with activated charcoal and reheaters on the exhaust gas emissions of common rail type diesel engines. The effect obtained was a decrease in CO emission results from 0.05 to 0.01 with a percentage decrease of 80% and Opacity from 32 to 23 by 28%